Au Nanoparticles on 4-Thiophenol-Electrodeposited Carbon Surfaces for the Simultaneous Detection of 8-Hydroxyguanine and Guanine - Niloufar Soltani; Qusai Hassan; Meissam Noroozifar; Kagan Kerman (Chemosensors, 2023)
In this proof-of-concept study, gold nanoparticles (AuNPs) were immobilized on glassy carbon electrode (GCE) surfaces using a surface-anchored diazonium salt of 4-aminothiophenol (GCE-Ph-S-AuNPs). X-ray photoelectron spectroscopy (XPS) studies confirmed the attachment of the AuNPs via 4-thiophenol onto the surface of the modified electrode. Differential pulse voltammetry (DPV) was performed for the simultaneous determination of guanine (G) and 8-hydroxyguanine (8-OH-G). The calibration curves were linear up to 140 µM and 60 µM with a limit of detection of 0.02 µM and 0.021 µM for G and 8-OH-G, respectively. Moreover, chronoamperometric studies were carried out for the determination of diffusion coefficients of 8-OH-G and G. The GCE-Ph-S-AuNPs were also applied in genomic DNA-spiked samples for the determination of G and 8-OH-G with recovery rates between 98.5% and 103.3%. The novel electrochemical surface provided a potential platform for the sensitive detection of 8-OH-G related to oxidative stress-induced DNA damage in clinical studies.